A precipitant for sewage treatment

By using precipitants of modified polymerized metal silicate salts, modified polyacrylamide and other components in low-temperature sewage treatment, combined with the adsorption effect of biochar, the problem of poor low-temperature sewage treatment is solved, and efficient removal of various pollutants and the treatment cost is reduced.

CN119161002BActive Publication Date: 2025-03-28SHAANXI WATER DEVELOPMENT & ENVIRONMENTAL PROTECTION GROUP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411653040.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-28
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

In low-temperature environments, the sewage treatment effect is poor, resulting in high ammonia nitrogen effluent, sludge expansion, poor settlement, high effluent suspension, COD and total phosphorus exceeding the standard.

Method used

A precipitant for sewage treatment is adopted, which includes modified polymeric silicate metal salt, modified polyacrylamide, viscosity reducing agent, biochar and polyaspartic acid. The flocculation performance and charge stability are improved through the modification treatment, combined with the adsorption advantages of biochar, and the removal ability of organic macromolecules and heavy metal ions is enhanced.

Benefits of technology

It significantly reduces the SS, COD, NH3-N and TP content in the sewage, improves the quality of sewage treatment, reduces the dosage of agents and subsequent sludge treatment costs, and is suitable for low-temperature sewage treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application discloses a precipitant for sewage treatment, which relates to the field of sewage treatment technology. The precipitant includes 0.5-1 parts by mass of modified polysilicic acid metal salt, 0.06-0.1 parts by mass of modified polyacrylamide, 0.1-0.25 parts by mass of viscosity reducer, 1-3 parts by mass of biochar, and 0.01-0.02 parts by mass of polyaspartic acid, wherein the viscosity reducer is polyethylene glycol. The precipitant prepared in the present application can effectively reduce the SS, COD, NH3-N and TP contents in low-temperature sewage, greatly improve the treatment quality of low-temperature sewage, and lay a solid foundation for the subsequent reuse of water resources or standard discharge.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of sewage treatment, and in particular to a precipitant for sewage treatment. Background Art

[0002] The principle of using precipitants in sewage treatment is to add soluble chemicals to the sewage to react with certain dissolved substances in the water to generate insoluble or poorly soluble compounds that precipitate out, thereby achieving the purpose of purifying the water quality. This method is based on chemical reactions and mass transfer, and changes the chemical or physical properties of pollutants, transforming them from dissolved, colloidal or suspended states to precipitated or floating states, and then removing them from the water.

[0003] In urban sewage treatment, low-temperature sewage treatment in cold regions has always been a difficult point in water treatment. Low-temperature sewage mainly refers to winter urban sewage in towns north of 40 degrees north latitude in my country (generally 6~10℃, a few at 4~6℃).

[0004] In particular, sewage treatment plants in some small towns often have long pipe networks, mixed rainwater and sewage, and most pipes are laid along rivers. There may also be open channels and overhead pipes. Sewage is particularly prone to heat loss during flow, so the inlet temperature is often very low, with the lowest being only 3~6°C. For sewage treatment plants with an inlet temperature of only 3~6°C, the effluent quality will be seriously affected. The main manifestations are: high effluent ammonia nitrogen, sludge swelling, poor sedimentation, high effluent suspended solids, and excessive COD and total phosphorus.

[0005] The patent application document with publication number CN111410385A discloses a high-efficiency sewage treatment agent under low-temperature environment, including the following components in weight percentage: 43.8%~46.5% of polyaluminum ferrosilicate, 28.7%~30.6% of bentonite, 19.3%~20.9% of zeolite powder, and 4.9%~5.4% of diatomaceous earth.

[0006] The polyaluminium ferric silicate in the high-efficiency sewage treatment agent in the patent application document has poor flocculation performance at low temperatures. If it is directly put into sewage for use, it is prone to insufficient and uneven dissolution, which will affect its effect in sewage treatment. Summary of the invention

[0007] In order to improve the treatment effect of low-temperature sewage, the present application provides a precipitant for sewage treatment.

[0008] The present application provides a precipitant for sewage treatment, which adopts the following technical solution:

[0009] A precipitant for sewage treatment, comprising 0.5-1 parts by mass of modified polysilicate metal salt, 0.06-0.1 parts by mass of modified polyacrylamide, 0.1-0.25 parts by mass of a viscosity reducer, 1-3 parts by mass of biochar, and 0.01-0.02 parts by mass of polyaspartic acid, wherein the viscosity reducer is polyethylene glycol.

[0010] Preferably, the amount of the precipitant in each liter of sewage is: 100-200 mg of modified polysilicate metal salt, 12-20 mg of modified polyacrylamide, 20-50 mg of viscosity reducer, 200-600 mg of biochar, and 2-4 mg of polyaspartic acid.

[0011] Preferably, the method for using the precipitant comprises the following steps:

[0012] S1: 0.5-1 parts by mass of modified polysilicate metal salt is mixed with water to obtain a solution 1 with a concentration of 5-10 g / L;

[0013] S2: 0.06-0.1 parts by mass of modified polyacrylamide is mixed with water to obtain a solution 2 with a concentration of 1.5-2 g / L;

[0014] S3: 0.1-0.25 parts by mass of the viscosity reducer is mixed with water to obtain a solution 3 with a concentration of 5-10 g / L;

[0015] S4: dispersing 1 to 3 parts by mass of biochar in water to obtain a dispersion with a concentration of 20 to 40 g / L;

[0016] S5: 0.01-0.02 parts by mass of polyaspartic acid is mixed with water to obtain a solution 4 having a concentration of 0.4-0.6 g / L;

[0017] S6: uniformly mixing solution 1, solution 2, solution 3, the dispersion liquid and solution 4 to obtain a precipitant mixed solution;

[0018] The mass ratio of modified polysilicate metal salt, modified polyacrylamide, viscosity reducer, biochar and polyaspartic acid in the precipitant mixed solution is 0.5~1:0.06~0.1:0.1~0.25:1~3:0.01~0.02.

[0019] Preferably, the precipitant mixture is packaged and stored for subsequent use.

[0020] By adopting the above technical solution, the modified metal silicate is optimized in molecular structure, so that it can still maintain a certain activity and stabilize the charge at low temperature, which is conducive to the adsorption and flocculation of pollutants in sewage. After the introduction of modified polyacrylamide, the interaction between the modified polyacrylamide molecules and the modified metal silicate molecules can further increase the floc size, improve the sedimentation efficiency, and optimize the adsorption and removal of organic matter, reduce the shedding of organic matter, and reduce indicators such as the chemical oxygen demand of sewage.

[0021] In low-temperature sewage, the intermolecular forces of water are strong, which leads to an increase in the viscosity of sewage. The addition of viscosity reducers destroys the interaction between water molecules that is originally enhanced by low temperature, and reduces the viscosity of sewage. It also provides a certain amount of steric hindrance, so that the particles and organic matter in the sewage remain in a certain state of dispersion, avoiding their excessive aggregation due to the slowdown of molecular motion at low temperatures. In this dispersed state, modified polysilicate metal salts and modified polyacrylamide can be more evenly distributed in the sewage, and have a greater chance of interacting with particles and organic matter one by one, better playing their roles in charge neutralization, adsorption bridging, etc., forming flocs with a compact structure and appropriate size, which is more conducive to sedimentation.

[0022] For some difficult-to-degrade organic macromolecules or heavy metal ions, biochar can play its adsorption advantages and make up for the deficiencies of modified metal polysilicates and modified polyacrylamide in this regard, thereby broadening the overall adsorption range. In addition, after biochar adsorbs pollutants, these pollutants will accumulate on its surface and in its pores, resulting in increased local pollutant concentrations. In this case, the molecules of modified metal polysilicates and modified polyacrylamide are more likely to come into contact with high concentrations of pollutants, just like adsorption work in an "enriched area", greatly enhancing the overall adsorption effect.

[0023] During the flocculation process, biochar can also be filled inside the flocs formed by modified polyacrylamide, etc., to increase the density and mechanical strength of the flocs. Especially at low temperatures, the flocs are more likely to remain intact and will not break easily. The adsorption of biochar can also prevent pollutants on the surface of the flocs from falling back into the sewage, further improving the stability of the flocs and facilitating the sedimentation and separation of the flocs.

[0024] The functional groups (such as carboxyl) in the polyaspartic acid molecules can interact with the metal ions in the modified polysilicic acid metal salts and the active groups (such as amide) on the modified polyacrylamide molecular chains. This interaction can form a more complex and stable flocculation structure, just like building a more solid "bridge network", which can more effectively connect small particles in sewage, increase the size of flocs, and further enhance the flocculation effect.

[0025] In addition, polyaspartic acid can form stable complexes with calcium, magnesium and other ions in sewage, preventing them from forming scaling substances such as calcium carbonate and magnesium carbonate, thereby reducing equipment scaling.

[0026] Preferably, the preparation method of the modified polysilicate metal salt comprises the following steps:

[0027] S1: Mix the sodium silicate solution and the citric acid solution evenly, adjust the pH value to 3-4, and activate at room temperature for 60-90 minutes to obtain a polysilicic acid solution;

[0028] S2: After the metal salt solution is mixed evenly, a mixed solution is obtained, the mixed solution is added to the polysilicic acid solution, mixed evenly, and then the citric acid solution is added, mixed evenly, heated to 30-50°C, reacted for 3-5h, and then the citric acid solution is added again in the later stage of the reaction. The pH value is adjusted during the whole process to be maintained between 4 and 5, and the solution after the reaction is aged at room temperature for 22-26h, and dried to obtain a modified polysilicic acid metal salt;

[0029] The molar ratio of sodium silicate to total metal ions is 1-3:1.3-2.7;

[0030] The total molar number of the citric acid accounts for 20% to 40% of the total molar number of metal ions.

[0031] Preferably, the amount of the citric acid solution added three times is the same.

[0032] Preferably, the modified polysilicate metal salt is at least one of modified polysilicate aluminum iron, modified polysilicate aluminum zinc, and modified polysilicate aluminum iron zinc.

[0033] By adopting the above technical solution and adding citric acid three times, not only the flexibility of the molecular structure of the polysilicate metal salt is improved, but also the stability of the product, the dispersibility and solubility of the product, the controllability of the reaction and the consistency of the product performance are improved.

[0034] The first addition of citric acid can shorten the distance between silicate ions, promote the polymerization of silicate ions, and form a polysilicic acid solution, which provides a basic substance for the subsequent reaction with metal salts.

[0035] Adding citric acid at the beginning of the reaction can not only adjust the polymerization rate, but also affect the microstructure of the polysilicate metal salt, making the polymer metal body form a looser and more porous structure. This structure is conducive to the water molecules in the low-temperature sewage entering the polymer, thereby improving the solubility of the polysilicate metal salt.

[0036] The addition of citric acid in the later stage of the reaction is mainly for post-treatment of polysilicate metal salts. It can react with the metal ions or active sites remaining on the surface of the product, increase the surface charge of the product, and improve its dispersibility in the solution; further adjust the hydrophilicity of the product and optimize its solubility in low-temperature sewage.

[0037] Preferably, in the preparation of the modified polyaluminium ferrosilicate, the mixed solution comprises an aluminium sulfate solution and a ferric chloride solution, wherein the Al 3+ and Fe 3+ The molar ratio is 0.8~1.2:0.5~1.

[0038] Preferably, in the preparation of the modified polyaluminium zinc silicate, the mixed solution comprises an aluminium sulfate solution and a zinc chloride solution, wherein Al 3+ and Zn 2+ The molar ratio is 0.8~1.2:0.5~1.5.

[0039] Preferably, in the preparation of the modified polyaluminum iron zinc silicate, the mixed solution includes aluminum sulfate solution, ferric chloride solution and zinc chloride solution, and the aluminum in the mixed solution is 3+ , Fe 3+ and Zn 2+ The molar ratio is 0.8~1.2:0.7~0.9:0.4.

[0040] By adopting the above technical solution, the molar ratio of metal ions in the polysilicate metal salt is optimized, the flocculation efficiency of the modified polysilicate aluminum iron zinc can be improved, and the stability can be enhanced. At a lower dosage, a good sewage purification effect can be achieved, and the treatment cost can be reduced.

[0041] Preferably, the preparation method of the modified polyacrylamide comprises the following steps:

[0042] 1-3 mol of acrylamide, 0.5-1 mol of 2-acrylamide-2-methylpropanesulfonic acid, urea, sucrose and an initiator are dissolved in an ethanol aqueous solution, mixed evenly under an inert atmosphere, heated to 40-50°C, reacted for 4-6 hours, cooled, solid-liquid separated, washed, and dried to constant weight to obtain modified polyacrylamide;

[0043] The sucrose accounts for 0.5% to 1% of the total mass of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid;

[0044] The urea accounts for 1% to 3% of the total mass of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid.

[0045] Preferably, the initiator accounts for 0.3% to 0.5% of the total mass of acrylamide and 2-acrylamide-2-methylpropanesulfonic acid.

[0046] By adopting the above technical scheme, after adding urea and sucrose during the synthesis of polyacrylamide, on the one hand, the solubility and hydrophilicity of polyacrylamide are improved, thereby improving the performance of polyacrylamide at low temperatures. In low-temperature sewage, this modified polyacrylamide can maintain good dispersibility and will not lose its activity due to the decrease in temperature. It can effectively contact with pollutants in the sewage and carry out adsorption and flocculation.

[0047] On the other hand, the addition of urea and sucrose changes the molecular chain structure of polyacrylamide. The amino groups of urea combine with the amide groups on the polyacrylamide molecular chain, increasing the flexibility and extensibility of the molecular chain; the hydroxyl groups of sucrose form hydrogen bonds with the polyacrylamide molecules, enhancing the stability of the molecular chain. These changes allow polyacrylamide molecules to stretch better in sewage, thereby exposing more active groups. The stretching and structural changes of its molecular chain make it easier for the active groups to contact pollutants in sewage, thereby enhancing the adsorption and flocculation capabilities of pollutants.

[0048] Preferably, the precipitant further comprises 0.08-0.1 parts by mass of chitosan.

[0049] Preferably, 0.08-0.1 parts by mass of chitosan is uniformly mixed with an acetic acid aqueous solution to obtain a solution five with a concentration of 2 g / L-2.5 g / L, and the solution five can be added after the solution four.

[0050] Preferably, the mass fraction of the acetic acid aqueous solution is not less than 5%, and the mass fraction of acetic acid in the precipitant mixed solution is not less than 0.5%.

[0051] By adopting the above technical solution, the synergistic flocculation of chitosan, modified metal polysilicate and modified polyacrylamide can efficiently aggregate and precipitate suspended particles. This is because: on the one hand, chitosan can make up for the deficiencies of metal polysilicate in charge neutralization. For some suspended particles with complex surface charges, the combined use of the two agents can more effectively achieve charge balance and make the particles easier to aggregate. On the other hand, the long chain structure of chitosan can be entangled with the flocs formed by metal polysilicate, further increasing the size of the flocs and accelerating the precipitation rate.

[0052] The addition of chitosan can also work together with modified polyacrylamide. The amino and hydroxyl functional groups of chitosan can interact with the groups on modified polyacrylamide to enhance the attraction between molecules. Together, they can more firmly adsorb on suspended particles, improve the stability of flocs, and prevent flocs from breaking or redispersing during sedimentation.

[0053] The combination of chitosan and biochar adsorption can give full play to the adsorption advantages of both and adsorb different types of organic matter. This is based on the fact that chitosan itself has abundant amino and hydroxyl groups, which can form hydrogen bonds or chemical reactions with functional groups such as carboxyl and hydroxyl groups in organic matter for adsorption. At the same time, biochar also has a strong ability to adsorb organic matter, mainly through physical adsorption and chemical adsorption, and has a good adsorption effect on macromolecular organic matter and hydrophobic organic matter. Their combined action can more comprehensively remove organic matter in sewage and reduce chemical oxygen demand.

[0054] In summary, this application has the following beneficial effects:

[0055] 1. The precipitant used in this application can still maintain good flocculation performance and charge stability in low-temperature sewage by modifying polysilicate metal salts and polyacrylamide. After treatment with the precipitant, the SS, COD, NH3-N and TP contents in the sewage are significantly reduced, which shows that the precipitant has significant effects in removing various pollutants, greatly improving the treatment quality of low-temperature sewage, and laying a solid foundation for the subsequent reuse of water resources or discharge in compliance with standards.

[0056] 2. The precipitant used in this application, by further introducing chitosan, shows stronger adaptability and efficiency in low-temperature sewage treatment, can more effectively reduce the content of SS, COD, NH3-N and TP in sewage, and significantly improves the treatment quality of sewage.

[0057] 3. The precipitant of the present application can quickly remove a variety of pollutants in sewage, and only a small amount is needed to achieve a good treatment effect, thereby reducing the cost of purchasing, storing and transporting the agent. At the same time, the small amount of sludge produced is also small, which reduces the equipment operation cost of subsequent sludge treatment and the cost of secondary pollution treatment, which is conducive to saving overall costs. DETAILED DESCRIPTION

[0058] The present application is further described in detail below with reference to the embodiments.

[0059] In the following examples and preparations:

[0060] Biochar was purchased from Qizhong Chemical (Zhengzhou) Co., Ltd., with a particle size distribution of 0.5-1.5 mm;

[0061] Polyaspartic acid was purchased from Zhengzhou Jiahang Chemical Products Co., Ltd., industrial grade 99%.

[0062] Preparation Examples 1-3 Preparation of Polyaluminium Ferrosilicate

[0063] Preparation Example 1

[0064] S11: Accurately weigh a certain amount of sodium silicate solid, slowly add it to an appropriate amount of deionized water to prepare a sodium silicate solution with a concentration of 1 mol / L, add 0.09 L of 1 mol / L citric acid aqueous solution dropwise, stir and mix evenly, then add 1 mol / L dilute hydrochloric acid dropwise while stirring continuously, adjust the pH value to 3.0, and activate at room temperature for 60 min to obtain a polysilicic acid solution;

[0065] S12: Preparation of Al 3+ Aluminum sulfate solution with a concentration of 1 mol / L and Fe 3+ The 0.5 mol / L ferric chloride solution was mixed evenly, and then slowly added to the polysilicic acid solution. During the addition process, the solution should be continuously and moderately stirred to make it evenly mixed. The stirring speed was 200rmp, and then 0.09L of 1 mol / L citric acid aqueous solution was slowly added. During the addition process, it was also slowly stirred and mixed evenly, and the temperature of the system was maintained at 30°C. Under continuous stirring, the polymerization reaction was carried out for 5 hours. In the later stage of the polymerization reaction (1 hour away from the end of the reaction), 0.09L of 1 mol / L citric acid aqueous solution was slowly added. The pH value was adjusted with 10% ammonia water in the whole process and kept between 4 and 5. Then the solution after the reaction was allowed to stand and age for 22 hours at room temperature to obtain a polyaluminum ferric silicate solution. The polyaluminum ferric silicate solution was transferred to a vacuum drying oven, dried at 60°C for 8 hours, cooled, and slightly ground and dispersed to obtain a powdered modified polyaluminum ferric silicate.

[0066] Among them, the dosage of sodium silicate solution is 1L, the dosage of aluminum sulfate solution is 0.8L, the dosage of ferric chloride solution is 1L, and the dosage of citric acid accounts for about 20.8% of the total molar number of aluminum ions and iron ions.

[0067] Preparation Example 2

[0068] S11: Accurately weigh a certain amount of sodium silicate solid, slowly add it to an appropriate amount of deionized water to prepare a sodium silicate solution with a concentration of 1 mol / L, add 0.18 L of 1 mol / L citric acid aqueous solution dropwise, stir and mix evenly, then add 1 mol / L dilute hydrochloric acid dropwise while stirring continuously, adjust the pH value to 4, and activate at room temperature for 80 minutes to obtain a polysilicic acid solution;

[0069] S12: Preparation of Al 3+ Aluminum sulfate solution with a concentration of 1 mol / L and Fe 3+The 0.5 mol / L ferric chloride solution was mixed evenly, and then slowly added to the polysilicic acid solution. During the addition process, the solution should be continuously and moderately stirred at a stirring speed of 200 rpm. Then 0.18 L of 1 mol / L citric acid aqueous solution was slowly added dropwise. During the addition process, the mixture should also be slowly stirred and mixed evenly, and the temperature of the system was maintained at 40°C. The polymerization reaction was carried out for 4 hours under continuous stirring. In the late stage of the polymerization reaction (1 hour after the end of the reaction), 0.18 L of 1 mol / L citric acid aqueous solution was slowly added dropwise. The pH value was adjusted with 10% ammonia water in the whole process and maintained between 4 and 5. The reacted solution was then aged at room temperature for 24 hours to obtain a polyaluminum ferric silicate solution. The polyaluminum ferric silicate solution was transferred to a vacuum drying oven, dried at 60°C for 10 hours, cooled, and slightly ground and dispersed to obtain a powdered modified polyaluminum ferric silicate.

[0070] Among them, the amount of sodium silicate solution is 2L, the amount of aluminum sulfate solution is 1L, the amount of ferric chloride solution is 1.6L, and the amount of citric acid is about 30% of the total molar number of aluminum ions and iron ions.

[0071] Preparation Example 3

[0072] S11: Accurately weigh a certain amount of sodium silicate solid, slowly add it to an appropriate amount of deionized water to prepare a sodium silicate solution with a concentration of 1 mol / L, add 0.29 L of 1 mol / L citric acid aqueous solution dropwise, stir and mix evenly, then add 1 mol / L dilute hydrochloric acid dropwise while stirring continuously, adjust the pH value to 3.5, and activate at room temperature for 90 min to obtain a polysilicic acid solution;

[0073] S12: Preparation of Al 3+ Aluminum sulfate solution with a concentration of 1 mol / L and Fe 3+ Mix the 0.5 mol / L ferric chloride solution evenly, and then slowly add it to the polysilicic acid solution. During the addition process, the solution should be continuously and moderately stirred at a stirring speed of 200 rpm. Then slowly drop 0.29 L of 1 mol / L citric acid aqueous solution. During the addition process, slowly stir and mix evenly, and keep the temperature of the system at 50°C. Stir continuously to allow the polymerization reaction to take place for 3 hours. In the late stage of the polymerization reaction (1 hour after the end of the reaction), slowly drop 0.29 L of 1 mol / L citric acid aqueous solution. During the whole process, use 10% ammonia water to adjust the pH value and keep it between 4 and 5. The reacted solution is allowed to stand and age at room temperature for 26 hours to obtain a polyaluminum ferric silicate solution. The polyaluminum ferric silicate solution is transferred to a vacuum drying oven, dried at 60°C for 12 hours, cooled, and lightly ground and dispersed to obtain a powdered modified polyaluminum ferric silicate.

[0074] Among them, the amount of sodium silicate solution is 3L, the amount of aluminum sulfate solution is 1.2L, the amount of ferric chloride solution is 2L, and the amount of citric acid accounts for about 39.5% of the total molar number of aluminum ions and iron ions.

[0075] Preparation Examples 4-6 Preparation of Polyaluminium Zinc Silicate

[0076] Preparation Example 4

[0077] S11: Accurately weigh a certain amount of sodium silicate solid, slowly add it to an appropriate amount of deionized water to prepare a sodium silicate solution with a concentration of 1 mol / L, add 0.09 L of 1 mol / L citric acid aqueous solution dropwise, stir and mix evenly, then add 1 mol / L dilute hydrochloric acid dropwise while stirring continuously, adjust the pH value to 3.0, and activate at room temperature for 60 min to obtain a polysilicic acid solution;

[0078] S12: Preparation of Al 3+ Aluminum sulfate solution with a concentration of 1 mol / L and Zn 2+ The 0.5 mol / L zinc chloride solution was mixed evenly, and then slowly added to the polysilicic acid solution. During the addition process, the solution should be continuously and moderately stirred to make it evenly mixed. The stirring speed was 200rmp. Then 0.09L of 1mol / L citric acid aqueous solution was slowly added. During the addition process, it was also slowly stirred and mixed evenly, and the temperature of the system was maintained at 30°C. Under continuous stirring, the polymerization reaction was carried out for 5 hours. In the later stage of the polymerization reaction (1 hour away from the end of the reaction), 0.09L of 1mol / L citric acid aqueous solution was slowly added. The pH value was adjusted with 10% ammonia water in the whole process and kept between 4 and 5. Then the solution after the reaction was allowed to stand and age for 22 hours at room temperature to obtain a polyaluminum zinc silicate solution. The polyaluminum zinc silicate solution was transferred to a vacuum drying oven, dried at 60°C for 8 hours, cooled, and slightly ground and dispersed to obtain a powdered modified polyaluminum zinc silicate.

[0079] Among them, the dosage of sodium silicate solution is 1L, the dosage of aluminum sulfate solution is 0.8L, the dosage of zinc chloride solution is 1L, and the dosage of citric acid accounts for about 20.8% of the total molar number of aluminum ions and zinc ions.

[0080] Preparation Example 5

[0081] S11: Accurately weigh a certain amount of sodium silicate solid, slowly add it to an appropriate amount of deionized water to prepare a sodium silicate solution with a concentration of 1 mol / L, add 0.2 L of 1 mol / L citric acid aqueous solution dropwise, stir and mix evenly, then add 1 mol / L dilute hydrochloric acid dropwise while stirring continuously, adjust the pH value to 3.0, and activate at room temperature for 80 min to obtain a polysilicic acid solution;

[0082] S12: Preparation of Al 3+ Aluminum sulfate solution with a concentration of 1 mol / L and Zn 2+ The 0.5 mol / L zinc chloride solution was mixed evenly, and then slowly added to the polysilicic acid solution. During the addition process, the solution should be continuously and moderately stirred to make it evenly mixed. The stirring speed was 200rmp. Then 0.2L of 1 mol / L citric acid aqueous solution was slowly added. During the addition process, it was also slowly stirred and mixed evenly, and the temperature of the system was kept at 40°C. Under continuous stirring, the polymerization reaction was carried out for 4 hours. In the later stage of the polymerization reaction (1 hour after the end of the reaction), 0.2L of 1 mol / L citric acid aqueous solution was slowly added. The pH value was adjusted with 10% ammonia water in the whole process and kept between 4 and 5. Then the reacted solution was aged at room temperature for 24 hours to obtain a polyaluminum zinc silicate solution. The polyaluminum zinc silicate solution was transferred to a vacuum drying oven, dried at 60°C for 10 hours, cooled, and slightly ground and dispersed to obtain a powdered modified polyaluminum zinc silicate.

[0083] Among them, the dosage of sodium silicate solution is 2L, the dosage of aluminum sulfate solution is 1L, the dosage of zinc chloride solution is 2L, and the dosage of citric acid accounts for about 30% of the total molar number of aluminum ions and zinc ions.

[0084] Preparation Example 6

[0085] S11: Accurately weigh a certain amount of sodium silicate solid, slowly add it to an appropriate amount of deionized water to prepare a sodium silicate solution with a concentration of 1 mol / L, add 0.36 L of 1 mol / L citric acid aqueous solution dropwise, stir and mix evenly, then add 1 mol / L dilute hydrochloric acid dropwise while stirring continuously, adjust the pH value to 3.0, and activate at room temperature for 90 min to obtain a polysilicic acid solution;

[0086] S12: Preparation of Al 3+ Aluminum sulfate solution with a concentration of 1 mol / L and Zn 2+The 0.5 mol / L zinc chloride solution was mixed evenly, and then slowly added to the polysilicic acid solution. During the addition process, the solution should be continuously and moderately stirred to make it evenly mixed. The stirring speed was 200rmp. Then 0.36L of 1 mol / L citric acid aqueous solution was slowly added. During the addition process, it was also slowly stirred and mixed evenly, and the temperature of the system was maintained at 50°C. Under continuous stirring, the polymerization reaction was carried out for 3 hours. In the later stage of the polymerization reaction (1 hour away from the end of the reaction), 0.36L of 1 mol / L citric acid aqueous solution was slowly added. The pH value was adjusted with 10% ammonia water in the whole process and kept between 4 and 5. Then the reacted solution was allowed to stand and age for 26 hours at room temperature to obtain a polyaluminum zinc silicate solution. The polyaluminum zinc silicate solution was transferred to a vacuum drying oven, dried at 60°C for 14 hours, cooled, and slightly ground and dispersed to obtain a powdered modified polyaluminum zinc silicate.

[0087] Among them, the amount of sodium silicate solution is 3L, the amount of aluminum sulfate solution is 1.2L, the amount of zinc chloride solution is 3L, and the amount of citric acid accounts for about 40% of the total molar number of aluminum ions and zinc ions.

[0088] Preparation Examples 7-9 Preparation of Polysilicic Aluminum Iron Zinc

[0089] Preparation Example 7

[0090] S11: Accurately weigh a certain amount of sodium silicate solid, slowly add it to an appropriate amount of deionized water to prepare a sodium silicate solution with a concentration of 1 mol / L, add 0.13 L of 1 mol / L citric acid aqueous solution dropwise, stir and mix evenly, then add 1 mol / L dilute hydrochloric acid dropwise while stirring continuously, adjust the pH value to 3.0, and activate at room temperature for 60 min to obtain a polysilicic acid solution;

[0091] S12: Preparation of Al 3+ Aluminum sulfate solution with a concentration of 1 mol / L, Fe 3+ The concentration of 0.5 mol / L ferric chloride solution and Zn 2+The 0.5 mol / L zinc chloride solution was mixed evenly, and then slowly added to the polysilicic acid solution. During the addition process, the solution should be continuously and moderately stirred to make it evenly mixed. The stirring speed was 200rmp. Then 0.13L of 1mol / L citric acid aqueous solution was slowly added. During the addition process, it was also slowly stirred and mixed evenly, and the temperature of the system was maintained at 30°C. Under continuous stirring, the polymerization reaction was carried out for 5 hours. In the later stage of the polymerization reaction (1 hour away from the end of the reaction), 0.13L of 1mol / L citric acid aqueous solution was slowly added. The pH value was adjusted with 10% ammonia water in the whole process and kept between 4 and 5. Then the reacted solution was aged at room temperature for 22 hours to obtain a polysilicate aluminum iron zinc solution. The polysilicate aluminum iron zinc solution was transferred to a vacuum drying oven, dried at 60°C for 9 hours, cooled, and slightly ground and dispersed to obtain a powdered modified polysilicate aluminum iron zinc.

[0092] Among them, the amount of sodium silicate solution is 1L, the amount of aluminum sulfate solution is 0.8L, the amount of ferric chloride solution is 1.4L, the amount of zinc chloride solution is 0.8L, and the amount of citric acid accounts for about 20.5% of the total molar number of aluminum ions, iron ions and zinc ions.

[0093] Preparation Example 8

[0094] S11: Accurately weigh a certain amount of sodium silicate solid, slowly add it to an appropriate amount of deionized water to prepare a sodium silicate solution with a concentration of 1 mol / L, add 0.22 L of 1 mol / L citric acid aqueous solution dropwise, stir and mix evenly, then add 1 mol / L dilute hydrochloric acid dropwise while stirring continuously, adjust the pH value to 3.0, and activate at room temperature for 80 min to obtain a polysilicic acid solution;

[0095] S12: Preparation of Al 3+ Aluminum sulfate solution with a concentration of 1 mol / L, Fe 3+ The concentration of 0.5 mol / L ferric chloride solution and Zn 2+The 0.5 mol / L zinc chloride solution was mixed evenly, and then slowly added to the polysilicic acid solution. During the addition process, the solution should be continuously and moderately stirred to make it evenly mixed. The stirring speed was 200rmp. Then 0.22L of 1mol / L citric acid aqueous solution was slowly added. During the addition process, it was also slowly stirred and mixed evenly, and the temperature of the system was kept at 40°C. Under continuous stirring, the polymerization reaction was carried out for 4h. In the later stage of the polymerization reaction (1h away from the end of the reaction), 0.22L of 1mol / L citric acid aqueous solution was slowly added. The pH value was adjusted with 10% ammonia water in the whole process and kept between 4 and 5. Then the reacted solution was aged at room temperature for 24h to obtain a polyaluminum silicate iron zinc solution. The polyaluminum silicate iron zinc solution was transferred to a vacuum drying oven, dried at 60°C for 11h, cooled, and slightly ground and dispersed to obtain a powdered modified polyaluminum silicate iron zinc.

[0096] Among them, the amount of sodium silicate solution is 2L, the amount of aluminum sulfate solution is 1L, the amount of ferric chloride solution is 1.6L, the amount of zinc chloride solution is 0.8L, and the amount of citric acid accounts for about 30% of the total molar number of aluminum ions, iron ions and zinc ions.

[0097] Preparation Example 9

[0098] S11: Accurately weigh a certain amount of sodium silicate solid, slowly add it to an appropriate amount of deionized water to prepare a sodium silicate solution with a concentration of 1 mol / L, add 0.33 L of 1 mol / L citric acid aqueous solution dropwise, stir and mix evenly, then add 1 mol / L dilute hydrochloric acid dropwise while stirring continuously, adjust the pH value to 3.0, and activate at room temperature for 90 minutes to obtain a polysilicic acid solution;

[0099] S12: Preparation of Al 3+ Aluminum sulfate solution with a concentration of 1 mol / L, Fe 3+ The concentration of 0.5 mol / L ferric chloride solution and Zn 2+The 0.5 mol / L zinc chloride solution was mixed evenly, and then slowly added to the polysilicic acid solution. During the addition process, the solution should be continuously and moderately stirred to make it evenly mixed. The stirring speed was 200rmp. Then 0.33 L of 1 mol / L citric acid aqueous solution was slowly added. During the addition process, it was also slowly stirred and mixed evenly, and the temperature of the system was maintained at 50°C. Under continuous stirring, the polymerization reaction was carried out for 3 hours. In the later stage of the polymerization reaction (1 hour after the end of the reaction), 0.33 L of 1 mol / L citric acid aqueous solution was slowly added. The pH value was adjusted with 10% ammonia water in the whole process and kept between 4 and 5. Then the reacted solution was allowed to stand and age for 26 hours at room temperature to obtain a polyaluminum silicate iron zinc solution. The polyaluminum silicate iron zinc solution was transferred to a vacuum drying oven, dried at 60°C for 13 hours, cooled, and slightly ground and dispersed to obtain a powdered modified polyaluminum silicate iron zinc.

[0100] Among them, the amount of sodium silicate solution is 3L, the amount of aluminum sulfate solution is 1.2L, the amount of ferric chloride solution is 1.8L, the amount of zinc chloride solution is 0.8L, and the amount of citric acid accounts for about 30% of the total molar number of aluminum ions, iron ions and zinc ions.

[0101] Preparation Examples 10-12 Preparation of Modified Polyacrylamide

[0102] Preparation Example 10

[0103] 0.1 mol of acrylamide, 0.05 mol of 2-acrylamide-2-methylpropanesulfonic acid, sucrose, urea and ammonium persulfate are placed in a reactor, and 200 ml of 40% ethanol aqueous solution by mass is added. Under a nitrogen atmosphere, the mixture is stirred and mixed evenly, and the temperature is raised to 40°C. The mixture is reacted for 5 hours. After cooling, 20 ml of anhydrous ethanol is added dropwise, and the mixture is stirred and mixed evenly at a stirring speed of 100 rpm. After standing for 1 hour, the mixture is filtered under reduced pressure (-0.05 MPa), and washed twice with 2 times the amount of anhydrous ethanol. The mixture is dried to constant weight at 70°C in a vacuum drying oven, cooled, and lightly ground and dispersed to obtain modified polyacrylamide.

[0104] Among them, the amount of sucrose used is 0.5% of the total mass of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid, the amount of ammonium persulfate used is 0.3% of the total mass of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid, and the amount of urea used is 1% of the total mass of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid.

[0105] Preparation Example 11

[0106] 0.2 mol of acrylamide, 0.08 mol of 2-acrylamide-2-methylpropanesulfonic acid, sucrose, urea and ammonium persulfate are placed in a reactor, 400 ml of 40% ethanol aqueous solution by mass is added, and the mixture is stirred and mixed evenly under a nitrogen atmosphere. The mixture is heated to 50°C and reacted for 4 hours. After cooling, 35 ml of anhydrous ethanol is added dropwise and stirred and mixed evenly at a stirring speed of 100 rpm. After standing for 1 hour, the mixture is filtered under reduced pressure (-0.05 MPa), and washed twice with 2 times the amount of anhydrous ethanol. The mixture is dried to constant weight at 70°C in a vacuum drying oven, cooled, and lightly ground and dispersed to obtain modified polyacrylamide.

[0107] Among them, the amount of sucrose used is 0.8% of the total mass of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid, the amount of ammonium persulfate used is 0.4% of the total mass of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid, and the amount of urea used is 2% of the total mass of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid.

[0108] Preparation Example 12

[0109] 0.3 mol of acrylamide, 0.1 mol of 2-acrylamide-2-methylpropanesulfonic acid, sucrose, urea and ammonium persulfate are placed in a reactor, 500 ml of 40% ethanol aqueous solution by mass is added, and the mixture is stirred and mixed evenly under a nitrogen atmosphere. The mixture is heated to 50°C and reacted for 4 hours. After cooling, 50 ml of anhydrous ethanol is added dropwise and stirred and mixed evenly at a stirring speed of 100 rmp. After standing for 1 hour, the mixture is filtered under reduced pressure (-0.05 MPa), and washed twice with 2 times the amount of anhydrous ethanol. The mixture is dried to constant weight at 70°C in a vacuum drying oven, cooled, and lightly ground and dispersed to obtain modified polyacrylamide.

[0110] Among them, the amount of sucrose used is 1% of the total mass of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid, the amount of ammonium persulfate used is 0.5% of the total mass of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid, and the amount of urea used is 3% of the total mass of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid.

[0111] An embodiment of a precipitant for sewage treatment in the present application is as follows:

[0112] Example 1

[0113] This embodiment provides a precipitant for sewage treatment. Based on the dosage per liter of sewage, the precipitant includes 100 mg of modified polyaluminum ferrosilicate, 12 mg of modified polyacrylamide, 20 mg of polyethylene glycol, 200 mg of biochar, and 2 mg of polyaspartic acid.

[0114] This embodiment also provides a method for using the above-mentioned sewage precipitant, comprising the following steps:

[0115] S1: Add 20 ml of clean water to a container with a stirrer, start stirring at a speed of 100 rpm, slowly add 100 mg of modified polyaluminium ferrosilicate, stir for 5 min, increase the stirring speed to 200 rpm, and continue stirring until it is completely dissolved, which takes about 20 min to obtain a uniform solution 1 with a concentration of 5 g / L;

[0116] S2: Add 8 ml of clean water to another container with a stirrer, start stirring at 80 rpm, slowly add 12 mg of modified polyacrylamide, stir for 2 min, increase the stirring speed to 150 rpm, stir for 3 min, and finally increase the stirring speed to 200 rpm, continue stirring until completely dissolved, which takes about 15 min, to obtain a uniform solution II with a concentration of 1.5 g / L;

[0117] S3: Take another container with a stirrer, add 4 ml of clean water, start stirring at a speed of 150 rpm, slowly add 20 mg of polyethylene glycol, and continue stirring until it is completely dissolved, which takes about 8 minutes to obtain a uniform solution 3 with a concentration of 5 g / L;

[0118] S4: Take another container with a stirrer, add 10ml of water, start stirring, and set the stirring speed to 400rmp.

[0119] Slowly add 200 mg of biochar and continue stirring until the biochar is evenly distributed and the suspension is stable, which takes about 40 min to obtain a uniform dispersion with a concentration of 20 g / L;

[0120] S5: Take another container with a stirrer, add 5 ml of clean water, start stirring at a speed of 150 rpm, slowly add 2 mg of polyaspartic acid, and continue stirring until it is completely dissolved, which takes about 5 minutes to obtain a uniform solution 4 with a concentration of 0.4 g / L;

[0121] S6: slowly add solution 1, solution 2, solution 3, dispersion liquid and solution 4 into a larger container in sequence, while maintaining a stirring speed of 100 rpm to ensure uniform mixing, to obtain a precipitant mixed solution;

[0122] The mass ratio of modified polyaluminium ferrosilicate, modified polyacrylamide, polyethylene glycol, biochar and polyaspartic acid in the precipitant mixture is 0.5:0.06:0.1:1:0.01.

[0123] In the experiment, since the volume of the solution or dispersion of each component is small, the containers used in this experiment are all made of glass, and they are rinsed with clean water and dried before use; when transferring the solution or dispersion of each component, the operation should be slow and stable to avoid the solution sticking to the wall or splashing, and ensure that the solution can be accurately transferred to the target container. A small brush or a small amount of clean water can be used to transfer all the residues stuck to the weighing paper or the container wall.

[0124] Among them, the modified polyaluminum ferrosilicate comes from Preparation Example 1, and the modified polyacrylamide comes from Preparation Example 10.

[0125] Example 2

[0126] This embodiment provides a precipitant for sewage treatment. Based on the dosage per liter of sewage, the precipitant includes 150 mg of modified polyaluminum ferrosilicate, 16 mg of modified polyacrylamide, 35 mg of polyethylene glycol, 400 mg of biochar, and 3 mg of polyaspartic acid.

[0127] This embodiment also provides a method for using the above-mentioned sewage precipitant, comprising the following steps:

[0128] S1: Add 20 ml of clean water to a container with a stirrer, start stirring at a speed of 100 rpm, slowly add 150 mg of modified polyaluminium ferrosilicate, stir for 5 min, increase the stirring speed to 200 rpm, and continue stirring until it is completely dissolved, which takes about 30 min to obtain a uniform solution 1 with a concentration of 7.5 g / L;

[0129] S2: Add 9 ml of clean water to another container with a stirrer, start stirring at 80 rpm, slowly add 16 mg of modified polyacrylamide, stir for 2 min, increase the stirring speed to 150 rpm, stir for 3 min, and finally increase the stirring speed to 200 rpm, continue stirring until completely dissolved, which takes about 20 min, to obtain a uniform solution II with a concentration of 1.8 g / L;

[0130] S3: Take another container with a stirrer, add 5 ml of clean water, start stirring at a speed of 150 rpm, slowly add 35 mg of polyethylene glycol, and continue stirring until it is completely dissolved, which takes about 12 minutes to obtain a uniform solution 3 with a concentration of 7 g / L;

[0131] S4: Take another container with a stirrer, add 13 ml of water, start stirring, and set the stirring speed to 400 rpm.

[0132] Slowly add 400 mg of biochar and continue stirring until the biochar is evenly distributed and the suspension is stable, which takes about 60 min to obtain a uniform dispersion with a concentration of 30 g / L;

[0133] S5: Take another container with a stirrer, add 6 ml of clean water, start stirring at a speed of 150 rpm, slowly add 3 mg of polyaspartic acid, and continue stirring until it is completely dissolved, which takes about 7 minutes to obtain a uniform solution 4 with a concentration of 0.5 g / L;

[0134] S6: slowly add solution 1, solution 2, solution 3, dispersion liquid and solution 4 into a larger container in sequence, while maintaining a stirring speed of 100 rpm to ensure uniform mixing, to obtain a precipitant mixed solution;

[0135] The mass ratio of modified polyaluminium ferrosilicate, modified polyacrylamide, polyethylene glycol, biochar and polyaspartic acid in the precipitant mixture is 0.75:0.08:0.175:2:0.015.

[0136] In the experiment, since the volume of the solution or dispersion of each component is small, the containers used in this experiment are all made of glass, and they are rinsed with clean water and dried before use; when transferring the solution or dispersion of each component, the operation should be slow and stable to avoid the solution sticking to the wall or splashing, and ensure that the solution can be accurately transferred to the target container. A small brush or a small amount of clean water can be used to transfer all the residues stuck to the weighing paper or the container wall.

[0137] Among them, the modified polyaluminum ferrosilicate comes from Preparation Example 1, and the modified polyacrylamide comes from Preparation Example 10.

[0138] Example 3

[0139] This embodiment provides a precipitant for sewage treatment. Based on the dosage per liter of sewage, the precipitant includes 200 mg of modified polyaluminum ferrosilicate, 20 mg of modified polyacrylamide, 50 mg of polyethylene glycol, 600 mg of biochar, and 4 mg of polyaspartic acid.

[0140] This embodiment also provides a method for using the above-mentioned sewage precipitant, comprising the following steps:

[0141] S1: Add 20 ml of clean water to a container with a stirrer, start stirring at a speed of 100 rpm, slowly add 200 mg of modified polyaluminium ferrosilicate, stir for 5 min, increase the stirring speed to 200 rpm, and continue stirring until it is completely dissolved, which takes about 40 min to obtain a uniform solution 1 with a concentration of 10 g / L;

[0142] S2: Add 10 ml of clean water to another container with a stirrer, start stirring at 80 rpm, slowly add 20 mg of modified polyacrylamide, stir for 2 min, increase the stirring speed to 150 rpm, stir for 3 min, and finally increase the stirring speed to 200 rpm, continue stirring until completely dissolved, which takes about 25 min, to obtain a uniform solution II with a concentration of 2 g / L;

[0143] S3: Take another container with a stirrer, add 5 ml of clean water, start stirring at a speed of 150 rpm, slowly add 50 mg of polyethylene glycol, and continue stirring until it is completely dissolved, which takes about 15 minutes to obtain a uniform solution 3 with a concentration of 10 g / L;

[0144] S4: Take another container with a stirrer, add 15 ml of water, start stirring, and set the stirring speed to 400 rpm.

[0145] Slowly add 600 mg of biochar and continue stirring until the biochar is evenly distributed and the suspension is stable, which takes about 80 min to obtain a uniform dispersion with a concentration of 40 g / L;

[0146] S5: Take another container with a stirrer, add 7 ml of clean water, start stirring at a speed of 150 rpm, slowly add 4 mg of polyaspartic acid, and continue stirring until it is completely dissolved, which takes about 10 minutes to obtain a uniform solution 4 with a concentration of 0.6 g / L;

[0147] S6: slowly add solution 1, solution 2, solution 3, dispersion liquid and solution 4 into a larger container in sequence, while maintaining a stirring speed of 100 rpm to ensure uniform mixing, to obtain a precipitant mixed solution;

[0148] The mass ratio of modified polyaluminium ferrosilicate, modified polyacrylamide, polyethylene glycol, biochar and polyaspartic acid in the precipitant mixture is 1:0.1:0.25:3:0.02.

[0149] In the experiment, since the volume of the solution or dispersion of each component is small, the containers used in this experiment are all made of glass, and they are rinsed with clean water and dried before use; when transferring the solution or dispersion of each component, the operation should be slow and stable to avoid the solution sticking to the wall or splashing, and ensure that the solution can be accurately transferred to the target container. A small brush or a small amount of clean water can be used to transfer all the residues stuck to the weighing paper or the container wall.

[0150] Among them, the modified polyaluminum ferrosilicate comes from Preparation Example 1, and the modified polyacrylamide comes from Preparation Example 10.

[0151] Example 4

[0152] The difference between this embodiment and embodiment 3 is that the modified polyaluminum ferrosilicate comes from preparation example 2, and the modified polyacrylamide comes from preparation example 11.

[0153] The rest is the same as in Example 3.

[0154] Example 5

[0155] The difference between this embodiment and embodiment 4 is that:

[0156] Among them, the modified polyaluminum ferrosilicate comes from Preparation Example 3, and the modified polyacrylamide comes from Preparation Example 12.

[0157] The rest is the same as Example 4.

[0158] Example 6

[0159] The difference between this embodiment and embodiment 5 is that the modified polyaluminium iron silicate is replaced by modified polyaluminium zinc silicate;

[0160] Among them, the modified polyaluminum zinc silicate comes from Preparation Example 4, and the modified polyacrylamide comes from Preparation Example 10.

[0161] The rest is the same as Example 5.

[0162] Example 7

[0163] The difference between this embodiment and embodiment 6 is that:

[0164] Among them, the modified polyaluminum zinc silicate comes from Preparation Example 5, and the modified polyacrylamide comes from Preparation Example 11.

[0165] The rest is the same as Example 6.

[0166] Example 8

[0167] The difference between this embodiment and embodiment 7 is that:

[0168] Among them, the modified polyaluminum zinc silicate comes from Preparation Example 6, and the modified polyacrylamide comes from Preparation Example 12.

[0169] The rest is the same as Example 7.

[0170] Example 9

[0171] This embodiment provides a precipitant for sewage treatment. Based on the dosage per liter of sewage, the precipitant includes 150 mg of modified polyaluminum ferric silicate, 50 mg of modified polyaluminum zinc silicate, 20 mg of modified polyacrylamide, 50 mg of polyethylene glycol, 600 mg of biochar, and 4 mg of polyaspartic acid.

[0172] This embodiment also provides a method for using the above-mentioned sewage precipitant, comprising the following steps:

[0173] S1: Add 20 ml of clean water to a container with a stirrer, start stirring at a speed of 100 rpm, slowly add 150 mg of modified polyaluminum iron silicate and 50 mg of modified polyaluminum zinc silicate, stir for 5 min, increase the stirring speed to 200 rpm, and continue stirring until completely dissolved, which takes about 40 min to obtain a uniform solution 1 with a concentration of 10 g / L;

[0174] S2: Add 10 ml of clean water to another container with a stirrer, start stirring at 80 rpm, slowly add 20 mg of modified polyacrylamide, stir for 2 min, increase the stirring speed to 150 rpm, stir for 3 min, and finally increase the stirring speed to 200 rpm, continue stirring until completely dissolved, which takes about 25 min, to obtain a uniform solution II with a concentration of 2 g / L;

[0175] S3: Take another container with a stirrer, add 5 ml of clean water, start stirring at a speed of 150 rpm, slowly add 50 mg of polyethylene glycol, and continue stirring until it is completely dissolved, which takes about 15 minutes to obtain a uniform solution 3 with a concentration of 10 g / L;

[0176] S4: Take another container with a stirrer, add 15 ml of water, start stirring, and set the stirring speed to 400 rpm.

[0177] Slowly add 600 mg of biochar and continue stirring until the biochar is evenly distributed and the suspension is stable, which takes about 80 min to obtain a uniform dispersion with a concentration of 40 g / L;

[0178] S5: Take another container with a stirrer, add 7 ml of clean water, start stirring at a speed of 150 rpm, slowly add 4 mg of polyaspartic acid, and continue stirring until it is completely dissolved, which takes about 10 minutes to obtain a uniform solution 4 with a concentration of 0.6 g / L;

[0179] S6: slowly add solution 1, solution 2, solution 3, dispersion liquid and solution 4 into a larger container in sequence, while maintaining a stirring speed of 100 rpm to ensure uniform mixing, to obtain a precipitant mixed solution;

[0180] The mass ratio of modified polyaluminium ferric silicate, modified polyaluminium zinc silicate, modified polyacrylamide, polyethylene glycol, biochar and polyaspartic acid in the precipitant mixture is 0.75:0.25:0.1:0.25:3:0.02.

[0181] In the experiment, since the volume of the solution or dispersion of each component is small, the containers used in this experiment are all made of glass, and they are rinsed with clean water and dried before use; when transferring the solution or dispersion of each component, the operation should be slow and stable to avoid the solution sticking to the wall or splashing, and ensure that the solution can be accurately transferred to the target container. A small brush or a small amount of clean water can be used to transfer all the residues stuck to the weighing paper or the container wall.

[0182] Among them, the modified polyaluminum iron silicate comes from Preparation Example 2, the modified polyaluminum zinc silicate comes from Preparation Example 5, and the modified polyacrylamide comes from Preparation Example 11.

[0183] Example 10

[0184] The difference from Example 8 is that the modified polyaluminium zinc silicate is replaced by modified polyaluminium iron zinc silicate;

[0185] Among them, the modified polyaluminum iron zinc silicate comes from Preparation Example 7, and the modified polyacrylamide comes from Preparation Example 10.

[0186] The rest is the same as Example 8.

[0187] Embodiment 11

[0188] The difference from Example 10 is:

[0189] Among them, the modified polyaluminum iron zinc silicate comes from Preparation Example 8, and the modified polyacrylamide comes from Preparation Example 11.

[0190] The rest is the same as Example 10.

[0191] Example 12

[0192] The difference from Example 11 is:

[0193] Among them, the modified polyaluminum iron zinc silicate comes from Preparation Example 9, and the modified polyacrylamide comes from Preparation Example 12.

[0194] The rest is the same as Example 11.

[0195] Embodiment 13

[0196] This embodiment provides a precipitant for sewage treatment. Based on the dosage per liter of sewage, the precipitant includes 200 mg of modified polyaluminum iron zinc silicate, 20 mg of modified polyacrylamide, 50 mg of polyethylene glycol, 600 mg of biochar, 4 mg of polyaspartic acid and 16 mg of chitosan.

[0197] This embodiment also provides a method for using the above-mentioned sewage precipitant, comprising the following steps:

[0198] S1: Add 20 ml of clean water to a container with a stirrer, start stirring at a speed of 100 rpm, slowly add 200 mg of modified polyaluminum iron zinc silicate, stir for 5 min, increase the stirring speed to 200 rpm, and continue stirring until it is completely dissolved, which takes about 40 min to obtain a uniform solution 1 with a concentration of 10 g / L;

[0199] S2: Add 10 ml of clean water to another container with a stirrer, start stirring at 80 rpm, slowly add 20 mg of modified polyacrylamide, stir for 2 min, increase the stirring speed to 150 rpm, stir for 3 min, and finally increase the stirring speed to 200 rpm, continue stirring until completely dissolved, which takes about 25 min, to obtain a uniform solution II with a concentration of 2 g / L;

[0200] S3: Take another container with a stirrer, add 5 ml of clean water, start stirring at a speed of 150 rpm, slowly add 50 mg of polyethylene glycol, and continue stirring until it is completely dissolved, which takes about 15 minutes to obtain a uniform solution 3 with a concentration of 10 g / L;

[0201] S4: Take another container with a stirrer, add 15 ml of water, start stirring, and set the stirring speed to 400 rpm.

[0202] Slowly add 600 mg of biochar and continue stirring until the biochar is evenly distributed and the suspension is stable, which takes about 80 min to obtain a uniform dispersion with a concentration of 40 g / L;

[0203] S5: Take another container with a stirrer, add 7 ml of clean water, start stirring at a speed of 150 rpm, slowly add 4 mg of polyaspartic acid, and continue stirring until it is completely dissolved, which takes about 10 minutes to obtain a uniform solution 4 with a concentration of 0.6 g / L;

[0204] S6: Take another container with a stirrer, add 8 ml of 5% acetic acid aqueous solution, start stirring at a speed of 150 rpm, slowly add 16 mg of chitosan, and continue stirring until it is completely dissolved, which takes about 10 minutes to obtain a uniform solution V with a concentration of 2 g / L;

[0205] S7: slowly add solution 1, solution 2, solution 3, dispersion, solution 4 and solution 5 into a larger container in sequence, while maintaining a stirring speed of 100 rpm to ensure uniform mixing, to obtain a precipitant mixed solution;

[0206] The mass ratio of modified polyaluminum iron zinc silicate, modified polyacrylamide, polyethylene glycol, biochar, polyaspartic acid and chitosan in the precipitant mixture is 1:0.1:0.25:3:0.02:0.08.

[0207] In the experiment, since the volume of the solution or dispersion of each component is small, the containers used in this experiment are all made of glass, and they are rinsed with clean water and dried before use; when transferring the solution or dispersion of each component, the operation should be slow and stable to avoid the solution sticking to the wall or splashing, and ensure that the solution can be accurately transferred to the target container. A small brush or a small amount of clean water can be used to transfer all the residues stuck to the weighing paper or the container wall.

[0208] Finally, in the precipitant mixture, the mass fraction of acetic acid remains at about 0.6% after dilution, ensuring that chitosan will not precipitate in the mixture.

[0209] Among them, the modified polyaluminum iron zinc silicate comes from Preparation Example 8, and the modified polyacrylamide comes from Preparation Example 11.

[0210] Embodiment 14

[0211] The difference between this embodiment and embodiment 13 is that:

[0212] The dosage of chitosan is 20 mg;

[0213] The mass ratio of modified polyaluminum iron zinc silicate, modified polyacrylamide, polyethylene glycol, biochar, polyaspartic acid and chitosan in the precipitant mixture is 1:0.1:0.25:3:0.02:0.1.

[0214] The rest is the same as Example 13.

[0215] Comparative Example 1

[0216] The difference between this comparative example and Example 1 is:

[0217] The preparation method of modified polyaluminium ferrosilicate comprises the following steps:

[0218] S11: Accurately weigh a certain amount of sodium silicate solid, slowly add it to an appropriate amount of deionized water to prepare a sodium silicate solution with a concentration of 1 mol / L, stir and mix evenly, then add 1 mol / L dilute hydrochloric acid dropwise while stirring continuously, adjust the pH value to 3.0, and activate at room temperature for 60 minutes to obtain a polysilicic acid solution;

[0219] S12: Preparation of Al 3+ Aluminum sulfate solution with a concentration of 1 mol / L and Fe 3+The 0.5 mol / L ferric chloride solution was mixed evenly, and then slowly added to the polysilicic acid solution. During the addition process, the solution was continuously and moderately stirred to make it evenly mixed. The stirring speed was 200 rpm, and the temperature of the system was maintained at 30°C. The polymerization reaction was carried out for 5 hours under continuous stirring. During the whole process, the pH was adjusted with 10% ammonia water by mass and maintained between 4 and 5. The reacted solution was then aged at room temperature for 22 hours to obtain a polyaluminum ferric silicate solution. The polyaluminum ferric silicate solution was transferred to a vacuum drying oven, dried at 60°C for 8 hours, cooled, and lightly ground and dispersed to obtain powdered polyaluminum ferric silicate.

[0220] Among them, the dosage of sodium silicate solution is 1L, the dosage of aluminum sulfate solution is 0.8L, and the dosage of ferric chloride solution is 1L.

[0221] The modified polyacrylamide comes from Preparation Example 10.

[0222] The rest is the same as in Example 1.

[0223] Comparative Example 2

[0224] The difference between this comparative example and comparative example 1 is:

[0225] The preparation method of modified polyaluminium ferrosilicate comprises the following steps:

[0226] S11: Accurately weigh a certain amount of sodium silicate solid, slowly add it to an appropriate amount of deionized water to prepare a sodium silicate solution with a concentration of 1 mol / L, stir and mix evenly, then add 1 mol / L dilute hydrochloric acid dropwise while stirring continuously, adjust the pH value to 3.0, and activate at room temperature for 60 minutes to obtain a polysilicic acid solution;

[0227] S12: Preparation of Al 3+ Aluminum sulfate solution with a concentration of 1 mol / L and Fe 3+ The 0.5 mol / L ferric chloride solution was mixed evenly, and then slowly added to the polysilicic acid solution. During the addition process, the solution should be continuously and moderately stirred to make it evenly mixed. The stirring speed was 200rmp, and then 0.27L of 1 mol / L citric acid aqueous solution was slowly added. During the addition process, it was also slowly stirred and mixed evenly, and the temperature of the system was maintained at 30°C. Under constant stirring, the polymerization reaction was carried out for 5 hours. During the whole process, the pH was adjusted with 10% ammonia water and kept between 4 and 5. Then the reacted solution was allowed to stand and age for 22 hours at room temperature to obtain a polyaluminum ferric silicate solution. The polyaluminum ferric silicate solution was transferred to a vacuum drying oven, dried at 60°C for 8 hours, cooled, and slightly ground and dispersed to obtain a powdered modified polyaluminum ferric silicate.

[0228] Among them, the dosage of sodium silicate solution is 1L, the dosage of aluminum sulfate solution is 0.8L, the dosage of ferric chloride solution is 1L, and the dosage of citric acid accounts for about 20.8% of the total molar number of aluminum ions and iron ions.

[0229] Other details are the same as those in Comparative Example 1.

[0230] Comparative Example 3

[0231] The difference between this comparative example and comparative example 1 is:

[0232] Wherein, the preparation method of modified polyacrylamide comprises the following steps:

[0233] 0.1 mol acrylamide, 0.05 mol 2-acrylamide-2-methylpropanesulfonic acid, urea and ammonium persulfate are placed in a reaction kettle, and 200 ml of 40% ethanol aqueous solution is added. Under a nitrogen atmosphere, the mixture is stirred and mixed evenly, and the temperature is raised to 40°C. The mixture is reacted for 5 hours. After cooling, 20 ml of anhydrous ethanol is added dropwise, and the mixture is stirred and mixed evenly at a stirring speed of 100 rpm. After standing for 1 hour, the mixture is filtered under reduced pressure (-0.05 MPa), and washed twice with 2 times the amount of anhydrous ethanol. The mixture is dried to constant weight at 70°C in a vacuum drying oven, cooled, and lightly ground and dispersed to obtain powdered modified polyacrylamide.

[0234] Among them, the amount of ammonium persulfate used is 0.3% of the total mass of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid, and the amount of urea used is 1% of the total mass of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid.

[0235] Other details are the same as those in Comparative Example 1.

[0236] Comparative Example 4

[0237] The difference between this comparative example and Example 1 is:

[0238] No polyaspartic acid was added to the precipitant.

[0239] The rest is the same as in Example 1.

[0240] Performance Testing

[0241] Research object: A sewage treatment plant in a small town in northern Shaanxi.

[0242] On-site sampling of sewage samples before treatment at the sewage treatment plant was carried out. Sampling was carried out 3 times during the day and at night, with an interval of 4 hours each time. 5L was sampled each time. The pH fluctuation range was 6.5-8.5 and the temperature fluctuation range was 3-5℃. The 6 samples were placed in a larger container and stirred for about 10 minutes to obtain a mixed sewage sample. The pH of the mixed sample was about 7.5 and it was stored at 4℃.

[0243] (1) Prepare 18 clean glass containers with a capacity of 2 L and mark them clearly to distinguish them from each other. Accurately measure 1 L of the mixed sewage sample each time and carefully pour it into the marked 2 L glass container to prepare 18 samples. Under the condition that the speed of the stirring equipment is set to 150 rmp, the precipitant mixed solution in Examples 1 to 14 and Comparative Examples 1 to 4 is quickly added to each glass container containing the mixed sewage sample in sequence. After the addition of the precipitant mixed solution is completed, continue stirring for 1 to 2 minutes to allow the precipitant and sewage to fully mix and react. Then adjust the stirring speed to 50 rmp, continue stirring for 5 minutes, and let it stand for 60 minutes to allow the precipitate to fully degrade. Take the upper layer of clear water respectively, filter it through sand, and place it in a clean beaker for subsequent analysis of various indicators. The experimental environment is maintained at 3 to 5 ° C. The specific results are shown in Table 1.

[0244] Table 1 Water quality parameters after treatment with the precipitants in Examples 1 to 14 and Comparative Examples 1 to 4

[0245]

[0246] From the data in Table 1, we can see that:

[0247] By comparing and analyzing Examples 1 to 3 and Comparative Examples 1 to 4, it can be seen that by increasing the dosage of each component of the precipitant, the concentrations of suspended solids (SS), chemical oxygen demand (COD), ammonia nitrogen (NH3-N) and total phosphorus (TP) in the water quality parameters after treatment with the precipitant in Example 3 reach the discharge standard, indicating that at an appropriate dosage of the precipitant, efficient removal of suspended solids (SS), chemical oxygen demand (COD), ammonia nitrogen (NH3-N) and total phosphorus (TP) in sewage can be achieved.

[0248] Among them, by comparing and analyzing Example 1 and Comparative Examples 1 to 4, it can be seen that when synthesizing modified polyaluminum ferric silicate, adding citric acid three times can improve the solubility and flocculation properties of polyaluminum ferric silicate in low-temperature sewage, enhance the ability to remove organic matter, improve the phosphorus removal efficiency, broaden the scope of application, and reduce the risk of secondary pollution.

[0249] The use of sucrose to modify polyacrylamide makes the hydrophilicity and charge characteristics of polyacrylamide more prominent, improves the stability and density of the flocs, and can still maintain good sedimentation performance in a low temperature environment. At the same time, it helps to entrain ammonia nitrogen in the flocs and separate it from the water, reducing the ammonia nitrogen concentration and enhancing the phosphorus removal effect.

[0250] By comparing and analyzing Examples 3 to 5, it can be seen that by optimizing and adjusting the ratio of each component in the synthetic modified polyaluminum ferrosilicate, the contents of suspended solids (SS), chemical oxygen demand (COD), ammonia nitrogen (NH3-N) and total phosphorus (TP) in the treated wastewater are further reduced.

[0251] By comparing and analyzing Examples 3 to 9, it can be seen that the removal effect of COD and TP is better after replacing the modified polyaluminum iron silicate with modified polyaluminum zinc silicate, while the removal efficiency of SS and NH3-N is lower. This is mainly due to: on the one hand, zinc ions may form more stable complexes with certain organic matter, thereby promoting the precipitation or adsorption of organic matter. On the other hand, zinc ions can form insoluble compounds with phosphate ions, enhancing the phosphorus removal effect. In contrast, the hydrolysis products of iron ions and aluminum ions may be relatively weak in their ability to bind to pollutants.

[0252] Furthermore, after the modified polyaluminium zinc silicate and modified polyaluminium iron silicate were compounded, the removal effect of COD and TP was slightly improved. This is mainly because: modified polyaluminium zinc silicate may perform well in the adsorption of certain specific types of organic matter, while modified polyaluminium iron silicate has a better removal effect on other organic matter. After compounding, it can adsorb and remove different types of organic pollutants with a higher probability, thereby reducing the COD of sewage. Compared with using one of them alone, the adsorption capacity of organic matter after compounding is larger, the types and concentrations of metal ions are increased, and the complexation effect is more significant, which improves the removal efficiency of COD.

[0253] The flocs formed after compounding have a larger specific surface area and abundant surface functional groups, and have a stronger adsorption capacity for phosphate ions, further improving the removal effect of total phosphorus.

[0254] By comparing and analyzing Examples 9 to 12, it can be seen that after using modified polyaluminium-iron-zinc silicate to replace modified polyaluminium-iron silicate and modified polyaluminium-zinc silicate, the hydrolysis products of the three metal ions are more likely to interweave and promote each other, and the flocs formed are tighter, larger and more adsorbent than the flocs formed by using modified polyaluminium-iron silicate and modified polyaluminium-zinc silicate alone, which improves the removal effect of ammonia nitrogen and total phosphorus. And the reaction with phosphate ions is more efficient, and the total phosphorus in sewage can be removed by forming a more stable phosphate precipitate.

[0255] (2) Prepare two clean glass containers with a capacity of 2 L and make clear marks to distinguish each other. Accurately measure 1 L of the mixed sewage sample each time and carefully pour it into the marked 2 L glass container to prepare two samples. Use dilute hydrochloric acid with a mass fraction of 1 mol / L to adjust the pH of one sample to 6.5, and use ammonia water with a mass fraction of 10% to adjust the pH of the other sample to 8.5. Then, under the condition that the stirring speed of the stirring device is set to 150 rpm, the precipitant mixed solution in Example 14 is quickly added to each glass container containing the mixed sewage sample. After the addition of the precipitant mixed solution is completed, continue stirring for 1-2 minutes to allow the precipitant and sewage to fully mix and react. Then adjust the stirring speed to 50 rpm, continue stirring for 5 minutes, and let it stand for 60 minutes to allow the precipitate to fully degrade. Take the upper layer of clear water, filter it through sand, and place it in a clean beaker for subsequent analysis of various indicators. The experimental environment is maintained at 3-5°C. The specific results are shown in Table 2.

[0256] Table 2 Water quality parameters after treatment with the precipitant in Example 14 under different pH conditions

[0257]

[0258] Comparative analysis of the treatment results of sewage samples under different pH environments shows that the sewage treatment effect is better in a weak acid environment. This is mainly because: in a weak acid environment, the modified polysilicate aluminum iron zinc flocculation is relatively efficient and stable, and can better remove suspended matter and some soluble pollutants in sewage. At the same time, the weak acid environment is conducive to the protonation of the functional groups of some components of the precipitant, enhancing the adsorption between the precipitant and the pollutants.

Claims

1. A precipitant for sewage treatment, characterized in that: The precipitant comprises 0.5-1 parts by mass of modified polysilicate metal salt, 0.06-0.1 parts by mass of modified polyacrylamide, 0.1-0.25 parts by mass of viscosity reducer, 1-3 parts by mass of biochar, and 0.01-0.02 parts by mass of polyaspartic acid, wherein the viscosity reducer is polyethylene glycol; The preparation method of the modified polysilicate metal salt comprises the following steps: S1: Mix the sodium silicate solution and the citric acid solution evenly, adjust the pH value to 3-4, and activate at room temperature for 60-90 minutes to obtain a polysilicic acid solution; S2: After the metal salt solution is mixed evenly, a mixed solution is obtained, the mixed solution is added to the polysilicic acid solution, mixed evenly, and then the citric acid solution is added, mixed evenly, heated to 30-50°C, reacted for 3-5h, and then the citric acid solution is added again in the later stage of the reaction. The pH value is adjusted during the whole process to be maintained between 4 and 5, and the solution after the reaction is aged at room temperature for 22-26h, and dried to obtain a modified polysilicic acid metal salt; In the preparation method of the modified polymeric metal silicate, the molar ratio of sodium silicate to total metal ions is 1-3:1.3-2.7, and the total molar number of citric acid accounts for 20%-40% of the total molar number of metal ions.

2. The precipitant for sewage treatment according to claim 1, characterized in that: The modified polysilicate metal salt is at least one of modified polysilicate aluminum iron, modified polysilicate aluminum zinc, and modified polysilicate aluminum iron zinc.

3. The precipitant for sewage treatment according to claim 2, characterized in that: In the preparation of the modified polyaluminium ferrosilicate, the mixed solution includes an aluminium sulfate solution and a ferric chloride solution. 3+ and Fe 3+ The molar ratio is 0.8~1.2:0.5~1.

4. The precipitant for sewage treatment according to claim 3, characterized in that: In the preparation of the modified polyaluminium zinc silicate, the mixed solution includes an aluminium sulfate solution and a zinc chloride solution. 3+ and Zn 2+ The molar ratio is 0.8~1.2:0.5~1.

5.

5. The precipitant for sewage treatment according to claim 4, characterized in that: In the preparation of the modified polyaluminium-iron-zinc silicate, the mixed solution includes an aluminium sulfate solution, a ferric chloride solution and a zinc chloride solution. 3+ , Fe 3+ and Zn 2+ The molar ratio is 0.8~1.2:0.7~0.9:0.

4.

6. The precipitant for sewage treatment according to claim 5, characterized in that: The preparation method of the modified polyacrylamide comprises the following steps: 1-3 mol of acrylamide, 0.5-1 mol of 2-acrylamide-2-methylpropanesulfonic acid, urea, sucrose and an initiator are dissolved in an ethanol aqueous solution, mixed evenly under an inert atmosphere, heated to 40-50°C, reacted for 4-6 hours, cooled, solid-liquid separated, washed, and dried to constant weight to obtain modified polyacrylamide; The sucrose accounts for 0.5% to 1% of the total mass of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid; The urea accounts for 1% to 3% of the total mass of acrylamide and 2-acrylamide-2-methylpropane sulfonic acid.

7. The precipitant for sewage treatment according to claim 6, characterized in that: The precipitant also includes 0.08-0.1 parts by mass of chitosan.

Citation Information

Patent Citations

  • Efficient sewage treatment agent in low-temperature environment and method for treating sewage by using same

    CN111410385A

  • Coagulating sedimentation agent for treating low-temperature low-turbidity water

    CN103663650A

  • Environment-friendly sewage treating agent

    CN105776407A

  • Efficient sewage treatment flocculant and preparation method thereof

    CN112479327A